Implementasi Model Project Based Learning (PJBL) dalam Mengembangkan Kreativitas dan Berpikir Kreatif Siswa Sekolah Dasar - Nor Arefa Suro; Muaweroh; Safira Nur Aulia; Agung Setyawan (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
This study aims to analyze various scientific findings regarding the implementation of the Project-Based Learning (PjBL) model in the context of developing creativity and creative thinking in elementary school students. This study uses a literature review method, where data is collected and analyzed from various primary and secondary sources, such as national and international scientific journals, books, and other relevant research results published within the last five years. The focus of the study is to identify the key steps of PjBL that most effectively facilitate the dimensions of creativity (fluency, flexibility, originality, and detail) and to analyze the empirical impact of implementing this model at the elementary education level. The results of the literature synthesis indicate a consensus that PjBL is a highly effective pedagogical approach for enhancing elementary school students' creativity. This model provides an authentic framework, enabling students to address challenges, design innovative solutions, and manage projects independently, which directly stimulates their creative thinking processes. The findings indicate that the driving question and product evaluation aspects of PjBL are crucial factors in encouraging students to generate original ideas.